System performance of a composite stepped-slope floating breakwater - Lim, Chai Heng (2006)
With the increasing demand for multi-purpose use of coastal sea areas in recent years, the composite stepped-slope floating breakwater system (STEPFLOAT) has been designed and developed as an alternative engineering solution, mainly for shore protection and coastal shelter to pioneer the floating breakwater technology in Malaysia. The unique stepped-slope and multiple sharp-edge features of the STEPFLOAT serve to intercept waves by dissipating (rather than reflecting) the wave energy through the formation of wave breaking, turbulence and eddies around the polyhedron as the waves impinge on the surface of the structure. Laboratory experiments were conducted to study the performance of the STEPFLOAT as a wave attenuator under unidirectional monochromatic wave only environment on various system arrangements, i.e. 2-row, 3- row, G = b and G = 2b systems. A suggested mooring method using vertical piles as a modification to the classical mooring system using chains or cables is applied to the STEPFLOAT system to overcome the problem of roll and sway motions. Additional tests on the 2-row chain-moored STEPFLOAT were also conducted to allow comparisons with the fundamental design of the SSFBW system as well as the pilesupported STEPFLOAT. Experiments on restrained case for 2-row and 3-row systems were performed to evaluate the effect of heave and limited roll motions of the floating body on wave attenuation. For the present study, a simple conventional method is applied to decompose the co-existing composite wave record in front of the model into the incident and reflected waves. Transmitted wave heights were measured at the lee side of the model. Measured transmission coefficient (Ct), reflection coefficient (Cr) and loss coefficient (Cl) were related to the non-dimensional structural geometric parameters, i.e. relative width (B/L), relative draft (D/L) and relative pontoon spacing (G/L), and hydraulic parameters, i.e. wave steepness (H/L) and relative depth (d/L). Two new nondimensional composite parameters, i.e. BD number and BDG number were introduced and examined. Experimental results for Ct are presented and compared to the results of previous studies of various floating breakwater designs done by other researchers. Empirical equations for predicting the transmission coefficient are developed for each tested system using Multiple Linear Regression Analysis. The STEPFLOAT, with relatively smaller structure width, generally has excellent wave attenuation ability over most of the previous floating breakwaters. The experimental results showed that the composite pile-supported STEPFLOAT with 3-row, G = b and G = 2b arrangements are capable to attenuate waves up to 80% of the incident wave height for wave period of less than 1.33 seconds